Effect of Counseling on the Sexual Satisfaction Level of Women with Sexual Dysfunction using PLISSIT Model Focused on Dysfunctional Sexual Beliefs - Maliheh Mohammadzadeh Moghaddam; Maryam Moradi; Khadijeh Mirzaii Najmabadi; Mohammad Arash Ramezani; Mohammad Taghi Shakeri (Mashhad University of Medical Sciences, 2019)
Background: Sexual satisfaction plays a vital role in the stability of a marriage. Dysfunctional sexual beliefs are often overlooked despite their recognition as factors negatively affecting sexual function and sexual satisfaction.   Aim: This studyaimed to determine the effect of counseling based on the PLISSIT model focused on dysfunctional sexual beliefs on the sexual satisfaction level of women with sexual dysfunction. Method: This randomized controlled clinical trial was carried out on 61 married females with sexual dysfunction during 2018-2019. The data were collected using Sexual Dysfunctional Beliefs Questionnaire and Hudson's Index of Sexual Satisfaction. The intervention group received sexual counseling, whereas the control group received routine care. The data were analyzed in SPSS software (version 24) using the , Wilcoxon test, independent t-test, and Mann-Whitney U test. Results: The mean ages of the females in the intervention and control groups were 35.5±5.6 and 36.7±6.7 years, respectively. Mann-Whitney U test showed a significant increase in mean sexual satisfaction scores in the intervention group after the intervention, compared to scores before the intervention (2.8±7.7 vs. 0.3±2.3) (P=0.03). In addition, Mann-Whitney U revealed a significant decrease in the scores of sexual dysfunctional beliefs in the intervention group after the intervention, compared to the scores of the control group before the intervention (27.3±14.5 vs. 1.0±1.2) (P<0.001).   Implications for Practice: With regard to the positive effect of counseling on correcting sexual dysfunctional beliefs, it is recommended that counseling method be implemented to increase sexual satisfaction levels in women.